2023
DOI: 10.3390/electronics12030774
|View full text |Cite
|
Sign up to set email alerts
|

Facial Image Encryption for Secure Face Recognition System

Abstract: A biometric authentication system is more convenient and secure than graphical or textual passwords when accessing information systems. Unfortunately, biometric authentication systems have the disadvantage of being susceptible to spoofing attacks. Authentication schemes based on biometrics, including face recognition, are susceptible to spoofing. This paper proposes an image encryption scheme to counter spoofing attacks by integrating it into the pipeline of Linear Discriminant Analysis (LDA) based face recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Previous research performed face recognition with an image encryption scheme using XOR operations and pixel permutation with a randomization method. In addition, this research used LDA for the facial recognition algorithm [8]. This research showed that the proposed system only achieved an accuracy of 8.75%.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research performed face recognition with an image encryption scheme using XOR operations and pixel permutation with a randomization method. In addition, this research used LDA for the facial recognition algorithm [8]. This research showed that the proposed system only achieved an accuracy of 8.75%.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the signal is extremely sensitive to the change of system parameters and the disturbance of initial conditions [9]; [10]. Thus, chaotic systems provide a less consumption and higher speed means of implementing encryption tasks for large-scale data such as images [16]; [17]; [18], video and audio [11]; [19]. In order to combine chaotic systems with encryption algorithms, many properties of chaotic systems have been studied and developed [20]; [21]; [22]; [23]; [24]; [25]; [26].…”
Section: Introductionmentioning
confidence: 99%